The application of visual analytics to financial stability monitoring - Flood, Mark D.; Lemieux, Victoria L.; Varga, Margaret; William Wong, B.L. (Journal of Financial Stability, 2016)
This paper provides an overview of visual analytics—the science of analytical reasoning enhanced by interactive visualizations tightly coupled with data analytics software—and discusses its potential benefits in monitoring systemic financial stability. The core strength of visual analytics is to combine visualization's high-bandwidth information channel to the human analyst with the flexibility and power of rapid-iteration analytics. This combination is especially valuable in the context of macroprudential supervision, which is increasingly dominated by large volumes of dynamic and heterogeneous data. Our contribution is to describe and categorize the analytical challenges faced by macroprudential supervisors, and to indicate where and how visual analytics can increase supervisors’ comprehension of the data stream, helping to transform it into actionable knowledge to support informed decision- and policy-making. The paper concludes with suggestions for a research agenda.